Enhanced Recovery After Surgery implementation in practice: an ethnographic study of services for hip and knee replacement - Drew, S; Judge, A; Cohen, R; Fitzpatrick, R; Barker, K; Gooberman-Hill, R (BMJ Journals, 2019)
Objectives: Enhanced Recovery After Surgery (ERAS) programmes aim to improve care quality by optimising components of the care pathway and programmes for hip and knee replacement exist across the UK. However, there is variation in delivery and outcomes. This study aims to understand processes that influence implementation using the Consolidated Framework for Implementation Research (CFIR) to inform the design and delivery of services. Design: An ethnographic study using observations and interviews with staff involved in service delivery. Data were analysed using a thematic analysis, followed by an abductive approach whereby themes were mapped onto the 31 constructs and 5 domains of the CFIR. Setting: Four hospital sites in the UK delivering ERAS services for hip and knee replacement. Participants: 38 staff participated including orthopaedic surgeons, nurses and physiotherapists. Results: Results showed 17 CFIR constructs influenced implementation in all five domains. Within ‘intervention characteristics’, participants thought ERAS afforded advantages over alternative solutions and guidance was adaptable. In the ‘outer setting’, it was felt ERAS should be tailored to patients and education used to empower them in their recovery. However, there were concerns about postdischarge support and tensions with primary care. Within the ‘inner setting’, effective multidisciplinary collaboration was achieved by transferring knowledge about patients along the care pathway and multidisciplinary working practices. ERAS was viewed as a ‘message’ that had to be communicated consistently. There were concerns about resources and high volumes of patients. Staff access to information varied. At the domain ‘characteristics of individuals’, knowledge and beliefs impacted on implementation. Within ‘process’, involving opinion leaders in development and ‘champions’ who acted as a central point of contact, helped to engage staff. Formal and informal feedback helped to develop services. Conclusions: Findings demonstrate successful implementation involves empowering patients to work towards recovery, providing postdischarge support and promoting successful multidisciplinary team working.